Educational Leader’s Adversity Quotient, Management Style, and Job Performance: Implications to School Leadership - Louisa Anne Tansiongco; Florante Ibarra (Universitas Jambi, Indonesia, 2020)
The study examined the adversity quotient, school management style and job performance of public elementary school heads in Cabanatuan City, Philippines. Total population sampling was utilized among 38 public elementary school heads in the district. Anchored on Adversity Quotient Theory (Stoltz, 2000) and Situational Leadership Theory (Hersey & Blanchard, 2001), both processes measured how educational leader reacts and resolves within tough school related problems encountered. These lenses offered structure in looking at the four dimensions of adversity quotient in relation to leadership style. Survey questionnaire on Adversity Response Profile (ARP), Leadership Style, and Office/Individual Performance Commitment Response (OPCR) were utilized. With two-semester period of data consolidation, Pearson r product moment correlation assisted in the analysis of data. Results disclosed that, in adversity quotient and job performance, school heads having high degree of adversity quotient- control most likely to perform better in instructional leadership and quality standard for basic education program. Recommendations on the opportunity of assimilating adversity quotient and school management style in their current school head qualifications be considered to further improve organizational performance in the educational management system.